Farmers' organizations and CSA: a case study from Viet Nam - Simelton, Elisabeth (Food and Agriculture Organization of the United Nations, 2016)
The Compendium provides examples of more than 20 different approaches of how agricultural extension can support climate-smart agriculture, with contributions from seventeen institutions and over 30 contributors worldwide.